A Perikinetochoric Ring Defined by MCAK and Aurora-B as a Novel Centromere Domain - Parra, María Teresa (Public Library of Science, 2006)
Mitotic Centromere-Associated Kinesin (MCAK) is a member of the kinesin-13 subfamily of kinesin-related proteins. In mitosis, this microtubule-depolymerising kinesin seems to be implicated in chromosome segregation and in the correction of improper kinetochore-microtubule interactions, and its activity is regulated by the Aurora-B kinase. However, there are no published data on its behaviour and function during mammalian meiosis. We have analysed by immunofluorescence in squashed mouse spermatocytes, the distribution and possible function of MCAK, together with Aurora-B, during both meiotic divisions. Our results demonstrate that MCAK and Aurora-B colocalise at the inner domain of metaphase I centromeres. Thus, MCAK shows a “cone”-like three-dimensional distribution beneath and surrounding the closely associated sister kinetochores. During the second meiotic division, MCAK and Aurora-B also colocalise at the inner centromere domain as a band that joins sister kinetochores, but only during prometaphase II in unattached chromosomes. During chromosome congression to the metaphase II plate, MCAK relocalises and appears as a ring below each sister kinetochore. Aurora-B also relocalises to appear as a ring surrounding and beneath kinetochores but during late metaphase II. Our results demonstrate that the redistribution of MCAK at prometaphase II/metaphase II centromeres depends on tension across the centromere and/or on the interaction of microtubules with kinetochores. We propose that the perikinetochoric rings of MCAK and Aurora-B define a novel transient centromere domain at least in mouse chromosomes during meiosis. We discuss the possible functions of MCAK at the inner centromere domain and at the perikinetochoric ring during both meiotic divisions.